Pre-percutaneous coronary intervention sudden cardiac arrest in ST-elevation myocardial infarction: Incidence, predictors, and related outcomes - Machado, Guilherme Pinheiro; Theobald, Andre Luiz; de Araujo, Gustavo Neves; Silveira, Anderson Donelli da; Wainstein, Rodrigo Vugman; Fracasso, Julia Fagundes; Niches, Matheus; Chies, Angelo; Goncalves, Sandro Cadaval; Pimentel, Mauricio; Wainstein, Marco Vugman (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND: ST-segment elevation myocardial infarction (STEMI) is a frequent cause of sudden cardiac arrest (SCA) and early percutaneous coronary intervention (PCI) is associated with increased survival. Despite constant improvements in SCA management, survival remains poor. We aimed to assess pre-PCI SCA incidence and related outcomes in patients admitted with STEMI. METHODS: This was a prospective cohort study of patients admitted with STEMI in a tertiary university hospital over 11 years. All patients were submitted to emergency coronary angiography. Baseline characteristics, details of the procedure, reperfusion strategies, and adverse outcomes were assessed. The primary outcome was in-hospital mortality. The secondary outcome was 1-year mortality after hospital discharge. Predictors of pre-PCI SCA was also assessed. RESULTS: During the study period 1493 patients were included; the mean age was 61.1 years (±12), and 65.3% were male. Pre-PCI SCA was present in 133 (8.9%) patients. In-hospital mortality was higher in the pre-PCI SCA group (36.8% vs 8.8%, P<0.0001). In multivariate analysis, anterior MI, cardiogenic shock, age, pre-PCI SCA and lower ejection fraction remained significantly associated with in-hospital mortality. When we analyzed the interaction between pre-PCI SCA and cardiogenic shock upon admission there is a further increase in mortality risk when both conditions are present. For predictors of pre-PCI SCA, only younger age and cardiogenic shock remained significantly associated after multivariate analysis. Overall 1-year mortality rates were similar between pre-PCI SCA survivors and non-pre-PCI SCA group CONCLUSION: In a cohort of consecutive patients admitted with STEMI, pre-PCI SCA was associated with higher in-hospital mortality, and its association with cardiogenic shock further increases mortality risk. However, long-term mortality among pre-PCI SCA survivors was similar to non-SCA patients. Understanding characteristics associated with pre-PCI SCA may help to prevent and improve management of STEMI patients.